Arabidopsis shoot stem cells display dynamic transcription and DNA methylation patterns. (20th August 2020) - Gutzat, Ruben; Rembart, Klaus; Nussbaumer, Thomas; Hofmann, Falko; Pisupati, Rahul; Bradamante, Gabriele; Daubel, Nina; Gaidora, Angelika; Lettner, Nicole; Donà, Mattia; Nordborg, Magnus; Nodine, Michael; et al.
Abstract: In plants, aerial organs originate continuously from stem cells in the center of the shoot apical meristem. Descendants of stem cells in the subepidermal layer are progenitors of germ cells, giving rise to male and female gametes. In these cells, mutations, including insertions of transposable elements or viruses, must be avoided to preserve genome integrity across generations. To investigate the molecular characteristics of stem cells in Arabidopsis, we isolated their nuclei and analyzed stage‐specific gene expression and DNA methylation in plants of different ages. Stem cell expression signatures are largely defined by developmental stage but include a core set of stem cell‐specific genes, among which are genes implicated in epigenetic silencing. Transiently increased expression of transposable elements in meristems prior to flower induction correlates with increasing CHG methylation during development and decreased CHH methylation, before stem cells enter the reproductive lineage. These results suggest that epigenetic reprogramming may occur at an early stage in this lineage and could contribute to genome protection in stem cells during germline development. Synopsis: Only a few stem cells in a plant's shoot apical meristem serve as progenitors of the gametes that give rise to the next generation. Here, transcriptome and methylome analysis of pure populations of these stem cells from Arabidopsis reveals several unexpected results. Gene expression in stem cells is determined by the developmental stage of the plants. A core set of stem cell‐specific differentially‐expressed genes includes several that encode epigenetic regulators. Stage‐specific, transient expression of transposon‐related genes resembles that seen in gametes and gamete‐companion cells. Dynamic methylation at CHG and CHH sites of stem cell genomes indicates resetting of transposon silencing and early germ cell differentiation. Abstract : Stage‐specific transcriptomes and methylomes of pure plant stem cell populations suggests early occurrence of epigenetic reprogramming that may help genome protection.